Smart Belay Device for Sport Climbing—An Analysis about Falling - Heiko Oppel; Michael Munz (Engineering Proceedings)
Although sport climbing is generally considered a comparatively safe sport, the injuries that do occur can be more severe than in other sports. With its increased popularity over the last few decades, sport climbing has started to attract people who are unfamiliar with the sport. Especially as a belayer, you are responsible for the climber’s safety. For this reason, addressing the issue of safe belaying is necessary. Using an instrumented belay device, we recorded a climber’s fall into the rope with varying configurations. By combining this data with machine learning algorithms, we were able to categorize the recordings and extract information about the severity of the fall for the climber.